Shift in intelligence issue ownership: conceptualizing CITINT—intelligence conducted by citizens - Pietilä, Iikka; Kortesuo, Katleena; Pohjanen, Ulla; Tuominen, Mikko (Frontiers in Political Science, 2024)
This paper elaborates on the conceptualization of CITINT i.e. the intelligence activities conducted by citizens and NGO's. This paper is a preliminary attempt to establish foundation and perspectives for future research, and to provide for initial conceptualization of CITINT. Moreover, this paper elucidates CITINT's implications in legislative perspective within Finnish context. A semisystematic limited literature review incorporating academic literature, governmental outlets, and news was executed to explore the contexts and definitions regarding CITINT. Interviews with a journalist, an active CITINT individual, and a detective superintended of Finnish national bureau of investigation were conducted to clarify and provide backrest for conceptualization. The key contributions of this paper are further elucidation of CITINT as a concept and its implications. Moreover, this paper discusses the shift in power relations from centralized issue ownership of intelligence activities towards a more fragmented scene in which individuals and non-governmental organizations (NGO's) have more relevance, possibilities, and weight. Within CITINT, this paper points out the differentiation between governmentally facilitated CITINT and the bottom up CITINT conducted by individuals and NGOs on their own terms and tools. One key contribution of this paper is connecting CITINT to societal participation through the CCSCM framework. Although the interviews comprise an empirical component, support contextualization, and provide tangible examples, this paper's focus is on the theoretical and conceptual aspects of CITINT. The paper concludes with a discussion on the outlook, and possibilities and challenges of CITINT, and provokes questions for further discussion on the matter.